Preparation and optimization of a lignin-based pressure-sensitive adhesive - Jeanne Gendron; Charles Bruel; Yacine Boumghar; Daniel Montplaisir (MethodsX, 2023)
D-optimal designs were applied to find the best parameters for the preparation of lignin-based pressure-sensitive adhesives (PSA) for sticky notes. Organosolv lignin was directly incorporated into a polycarboxylate polyether (PCE)/water matrix. The independent variables considered in the experimental design were the ratio between PCE, lignin, and water and the curing parameters. The distance traveled by the ball (tack), the peel-off losses and the final water content were the analyzed responses that allowed the optimization of the PSA formulation. The accuracy, the precision and the efficiency of the model were evaluated during the first experimental design for the formulation of the lignin-based adhesive named DES-OL-ADH. This formulation was optimized during the second experimental design abbreviated DES-OL-OPT. The coefficients of determination of the tack, the peel-off losses and the final water content were 0.98, 0.99 and 0.99, respectively. The model was satisfactory which allows the optimization of the PSA formulation. The DES-OL-OPT suggests that lignin-based PSA can be prepared as a sticky note application with 5 wt% of lignin, 84 wt% of PCE and 11 wt% of added water in the oven at 130 °C for 60 min, which shows a higher tackiness and similar peel-off losses than the commercial sticky notes PSAs. • Protocol optimization for the preparation of a green pressure sensitive adhesive (PSA) from PCE polymer, lignin, and water. • Influence of 5 compositional or processing parameters on adhesive performance through a 2-steps d-optimal experimental design. • Development of a new method, based on peel-off losses, to assess the performance of a PSA.